Painting, patronage and collecting in England during the Civil Wars and Interregnum, c.1640-1660 - Burns, Emily (2019)
In the period from 1640 until 1660 England witnessed religious dispute, political dissent and military conflict which led to the overthrow of the monarchy and the foundation of a republic. This era of the English Civil War and Commonwealth and Protectorate governments has therefore come to be defined as a time of change and 'revolution' in a number of ways, including in the arts. However, there is evidence to suggest that this disruption to the status quo did not extend so deep into the established infrastructure of the 'art world' and habits of its players as has previously been asserted in art-historical assessments of the period.